2009
DOI: 10.1002/col.20506
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of color gamuts among several types of paper with the same printing technology

Abstract: In this work, we have studied the relationship among the colorimetric properties of different types of paper, having different finishing and grammage. Their color reproduction capability has also been analyzed by using the same printing technology (inkjet printing). On the one hand, we have plotted CIELAB data under the illuminant D50 into constant lightness and hue-angle planes to be compared with MacAdam limits and with Pointer's real-world surface color. On the other hand, we have calculated the volume gamu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…The widest color gamut was found on kraft liner coated with 1% nano-RHS, due to having the lowest TVI value for each process color (as shown in Fig. 9) and the best color details which resulted in the widest yellow line [45]. The narrow color gamut could be due to the pale color ink that penetrated into the paper, resulting in the dark tone increases.…”
Section: Print Quality On the Bleached Kraft Liners Coated With Nano-mentioning
confidence: 91%
“…The widest color gamut was found on kraft liner coated with 1% nano-RHS, due to having the lowest TVI value for each process color (as shown in Fig. 9) and the best color details which resulted in the widest yellow line [45]. The narrow color gamut could be due to the pale color ink that penetrated into the paper, resulting in the dark tone increases.…”
Section: Print Quality On the Bleached Kraft Liners Coated With Nano-mentioning
confidence: 91%
“…The results showed that color gamuts, ICC profiles and also light-fastness is influenced by paper properties. The effect of the colorimetric properties of different types of paper on the color gamut in inkjet printing was again studied [8]. No clear relationship among the colorimetric properties of paper such as the CIE whiteness index and the color gamut volume was found.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between paper and ink, its porosity, roughness, together with optical properties such as whiteness, opacity, light scattering, and gloss must be considered in the printing process [1][2]. The effect of paper properties on the final printed colors has been investigated for a variety of papers and printers, especially for inkjet printers [2][3][4][5][6][7][8][9][10]. However, this effect is not well understood yet and needs more researches.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 shows the differences between optimal reflectances and reflectances from a real color sample. However, optimal colors delimit the conventional color solid of human perception, and evaluate the colorimetric quality of colorants [10][11][12][13][14][15]: when colorants approach the MacAdam limits, a greater range of reproducible colors can be obtained (color gamut). For instance, in 1980 M. R. Pointer [16,17] used these colorimetric data to compare several industrial color gamuts.…”
Section: Introductionmentioning
confidence: 99%